Variable Inhibition of Zika Virus Replication by Different Wolbachia Strains in Mosquito Cell Cultures - Schultz, Michaela J. (J Virol, 2017)
Mosquito-borne arboviruses are a major source of human disease. One strategy to reduce arbovirus disease is to reduce the mosquito's ability to transmit virus. Mosquito infection with the bacterial endosymbiont Wolbachia pipientis wMel is a novel strategy to reduce Aedes mosquito competency for flavivirus infection. However, experiments investigating cyclic environmental temperatures have shown a reduction in maternal transmission of wMel, potentially weakening the integration of this strain into a mosquito population relative to that of other Wolbachia strains. Consequently, it is important to investigate additional Wolbachia strains. All Zika virus (ZIKV) suppression studies are limited to the wMel Wolbachia strain. Here we show ZIKV inhibition by two different Wolbachia strains: wAlbB (isolated from Aedes albopictus mosquitoes) and wStri (isolated from the planthopper Laodelphax striatellus) in mosquito cells. Wolbachia strain wStri inhibited ZIKV most effectively. Single-cycle infection experiments showed that ZIKV RNA replication and nonstructural protein 5 translation were reduced below the limits of detection in wStri-containing cells, demonstrating early inhibition of virus replication. ZIKV replication was rescued when Wolbachia was inhibited with a bacteriostatic antibiotic. We observed a partial rescue of ZIKV growth when Wolbachia-infected cells were supplemented with cholesterol-lipid concentrate, suggesting competition for nutrients as one of the possible mechanisms of Wolbachia inhibition of ZIKV. Our data show that wAlbB and wStri infection causes inhibition of ZIKV, making them attractive candidates for further in vitro mechanistic and in vivo studies and future vector-centered approaches to limit ZIKV infection and spread. IMPORTANCE Zika virus (ZIKV) has swiftly spread throughout most of the Western Hemisphere. This is due in large part to its replication in and spread by a mosquito vector host. There is an urgent need for approaches that limit ZIKV replication in mosquitoes. One exciting approach for this is to use a bacterial endosymbiont called Wolbachia that can populate mosquito cells and inhibit ZIKV replication. Here we show that two different strains of Wolbachia, wAlbB and wStri, are effective at repressing ZIKV in mosquito cell lines. Repression of virus growth is through the inhibition of an early stage of infection and requires actively replicating Wolbachia. Our findings further the understanding of Wolbachia viral inhibition and provide novel tools that can be used in an effort to limit ZIKV replication in the mosquito vector, thereby interrupting the transmission and spread of the virus.